Community Experience With Public Sex Offender Registries in the United States: A National Survey - Harris, Andrew J. R. (Criminal justice policy review, 2018)
Since the first sex offender community notification laws in the early 1990s, the expansion of online sex offender registries (SORs) in the United States has offered Americans unprecedented access to information about previously convicted sex offenders living in their communities. Despite this, survey data suggest that relatively few citizens use SORs and that even fewer use that information for specific protective purposes. The current study examines the patterns and correlates of SOR usage among a stratified nationwide sample of 1,000 U.S. adults, offering the most extensive national assessment to date of SOR use among the U.S. public. Although 45% of the sample reported that they had accessed an SOR (higher than rates reported in previous studies), the majority had done so only once or twice, most typically out of general curiosity rather than for a specific purpose. Separating these “casual users” from those who had consulted the SOR more frequently, the study revealed significant effects related to gender, age, race, political ideology, and importance of religion. Analyses also found the most frequent users to be significantly more likely to report diminished feelings of safety as a result of viewing SOR information and to engage in protective actions, including the sharing of information with family and neighbors. Policy implications for the design and implementation of public SORs are discussed.